2014
DOI: 10.1080/2156857x.2014.982158
|View full text |Cite
|
Sign up to set email alerts
|

Children with multiple stays at Nordic refuges for abused women: conclusions, challenges, and causes for concern

Abstract: This research was funded by ExtraStiftelsen ([grant number 2012/2/0246]) in collaboration with the Norwegian Council for Mental Health (Råde for psykisk helse). The research was hosted at the Norwegian Centre for Violence and Traumatic Stress Studies in Oslo and affiliated with the University of Bergen (Department of Education). I was also fortunate to join the National Research School for Teacher Education during my research process. Thank you for a knowledgeable and amazing three years. A special thanks to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 114 publications
0
9
0
Order By: Relevance
“…The purpose of the Shelter Act is to ensure the provision of good, comprehensive shelter services to women, men, and children who are subjected to domestic violence or threats of such violence (Bakketeig et al, 2014 ). In recent years, the focus on children in shelters has increased in both Norway and other Nordic countries (Selvik & Øverlien, 2014 ). Municipalities are obliged to offer adequate and appropriate accommodation at a shelter, as well as daytime services, such as advice, support, and guidance.…”
Section: Shelters For Victims Of Domestic Violence In Norwaymentioning
confidence: 99%
“…The purpose of the Shelter Act is to ensure the provision of good, comprehensive shelter services to women, men, and children who are subjected to domestic violence or threats of such violence (Bakketeig et al, 2014 ). In recent years, the focus on children in shelters has increased in both Norway and other Nordic countries (Selvik & Øverlien, 2014 ). Municipalities are obliged to offer adequate and appropriate accommodation at a shelter, as well as daytime services, such as advice, support, and guidance.…”
Section: Shelters For Victims Of Domestic Violence In Norwaymentioning
confidence: 99%
“…Studies have highlighted the impact of DVA on education and academic achievement, reporting behavioural difficulties, problems with school adjustment or absenteeism (Perkins and Graham‐Bermann, 2012). Moreover, living in refuge accommodation has additional effects (Holt et al ., 2008; Selvik and Øverlien, 2015). The impact of this can potentially remove many protective factors offered by school such as peer support and a stable educational environment (Wolfe et al ., 2003).…”
Section: Introductionmentioning
confidence: 99%
“…1 shows, statistics on children with multiple refuge relocations are available from 2003, with an interruption between 2008 and 2013; this interruption notwithstanding, it is evident that children with multiple relocations have made up a stable proportion (11%-17%) of all children at refuges over the years, with the exception of 2007 (24%) and 2015 (23%). Children made multiple stays at the same or different refuges for safety reasons (Bufdir, 2014(Bufdir, -2020Selvik & Øverlien, 2014).…”
Section: Children At Refuges For Abused Womenmentioning
confidence: 99%
“…But school absence and change of schools can be an additional challenge, potentially causing knowledge gaps, missed instruction, and interrupted social relations (Chanmugam & Teasley, 2014;Frederick & Goddard, 2010;Koutselini & Valanidou, 2014;Stanley, 2011). Selvik and Øverlien (2014) highlighted three fundamental challenges children with multiple refuge relocations face: prolonged and repeated experience of domestic violence, repeated disruptions to relationships, and repeated disruptions to school and preschool attendance. Based on the available literature on domestic violence and children, they concluded that these children are at risk of developing social and psychological difficulties, may have limited access to resources that could help develop their resilience to violence, and may fail or drop out of school.…”
Section: Previous Researchmentioning
confidence: 99%